Стильові напрямки в архітектурі Білорусі 1920–1930-х років - Шамрук, А. (Студії мистецтвознавчі, 2009)
The peculiarity of the style in the Western and Eastern parts of Belarus is accounted for the difference of socio-cultural context. Postсonstruсtivism in the architecture of Eastern parts of Belarus (1934–1941) is considered to be a style phenomenon formed by artistic-aesthetic, socio-ideological impulses of Socialist realism culture combining with neoclassical, constructivist manner, of Art Deco style. Neoclassical and avant-gardе trends mixed with Art Deco manner are developed in the architecture of Western Belarus.